ANALISIS SPASIAL KEJADIAN PENYAKIT KUSTA DI KABUPATEN BLORA PROVINSI JAWA TENGAH - Jati Kurniawan; Sunardi Radiono; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Spatial analysis of leprosy in BloraPurposeThis research aimed to discover the existence of leprosy agglomeration and factors causing leprosy.MethodThis research was an epidemiological study conducted in Blora. Data were analyzed using individual approach and spatial analysis.ResultsThere were clusters of leprosy cases at coordinates 7.215035 S and 111.535428 E radius of 10.54 km. Variables related to leprosy incidence were economic status and the distance of reservoir. The economic status obtained coefficient value -0.882169, error standard 0.372429, t-statistic -2.36869 and p-value 0.01881. While the distance of reservoir obtained coefficient value 0.00344507, standard error 0.000965419, t-statistic 3.56847 and p-value 0.00045.ConclusionThere were clusters of leprosy patients. There was a significant correlation between the variable of economic status and the distance of reservoir with the leprosy incidence. Health offices and related sectors need to provide informal skills training to leprosy patients for increasing family income.